Microbial quality assessment of selected marketed herbal medicinal formulations (Funded Work) - SEEMADEVI S. KADAM (International Journal of Pharma and Bio Sciences, 2019)
The use of herbal medicine has constantly been an element of human culture, as some plants possess significant remedial properties which can be used to heal diseases in humans and other animals. The widespread utilization of these herbal medicinal products in the healing and management of diseases within communities of Maharashtra, India has made it essential to examine the microbial quality of these products by taking into consideration the values set by regulatory bodies. The aim of present study was to evaluate the microbiological quality of selected marketed herbal medicinal formulations that are collected from the local market at Satara, Maharashtra. This study was therefore designed to evaluate the microbial quality of selected marketed herbal medicinal formulations which were collected from the local market at Satara, Maharashtra (India). Fifteen samples of marketed herbal medicinal formulations were collected from the retail pharmacy of Satara city. The examination of microbial load from all selected samples was carried out according to Indian Pharmacopoeia. Out of fifteen samples; fourteen samples were found to be contaminated with aerobic bacteria. The total aerobic bacterial count was beyond the prescribed limit given in IP whereas, all fifteen samples exhibited fungal contamination beyond acceptable limit Staphylococcus aureus was the most frequently isolated bacterium from 12 samples of marketed herbal medicinal formulations. Escherichia coli was found to be present followed in 4 samples, Salmonella typhi was found to be present in 3 samples, whereas, Pseudomonas aeruginosa was found in one sample. The current analysis signified the contamination of select marketed herbal medicinal formulations by microorganisms. Hence, such products can adversely affect health status of consumers as well as stability of the products. Therefore the quality assurance of these products should be thoroughly monitored during production and distribution of herbal drugs as well as Good Manufacturing Practices at Pharmaceutical level are legally required for the manufacturing of herbal medicinal products.